African Town : inspired by the true story of the last American slave ship - Latham, Irene; Waters, Charles, 1973-; Davis, Joycelyn M. (2022)
Chronicles the story of the last Africans brought illegally to the United States on the Clotilda in 1860.
Ages 12+.
Grades 7-9.
Keywords: Clotilda (Ship) -- Fiction; Novels in verse; Black people -- Africa -- Fiction; Slave trade -- Fiction; Africa -- Fiction; Africatown (Ala.) -- History -- 19th century -- Fiction; Novels in verse